Moving forward with service dominant logic: Exploring the strategic orientations of a service-centred view of the firm - Lucio Lamberti; Angela Paladino (International Journal of Business Science & Applied Management (IJBSAM), 2013)
Service Dominant Logic (SDL) has been the subject of great conceptual debate over the past years. We are now clearly at a crossroad where application is required to cement its practical relevance to the organization and its performance. This paper extends the SDL debate, as founded by Vargo and Lusch (2004), by analyzing it through the lens of strategic orientations, in combination with a service-centred view of the firm. In doing so, the purpose of this paper is twofold. Firstly we aim to identify the existence of common characteristics between SDL and existing conceptual orientations. Secondly, we go further to explore the conceptual relationships between these identified and empirically evaluated strategic orientations (market, resource, learning, service, and entrepreneurship orientations) and SDL theory. We proffer that a service-centred view of the firm requires the deployment of key facets of all of these strategic orientations. In this way, we argue that a SD orientation emerges that is in essence a strategic orientation combination. In doing so, we develop a comprehensive framework and lay the foundation for the initiation of empirical work on SDL to further enrich the work initiated by Vargo and Lusch (2004). The paper concludes with a discussion of this framework, its implications for scholars and practitioners and areas for future research.
Keywords: 650; service-dominant logic; strategic orientation; market orientation